PROSPEK PENGEMBANGAN USAHA INDUSTRI SEPATU KULIT DI KOTA PEKANBARU - Patiroi, Andi Achmad Alatas; Harahap, Azwar; Kornita, Sri Endang (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research was conducted in the city of Pekanbaru in May 2014 until October 2014. The purpose of this study was to determine how the prospects for business development in the leather shoe industry in Pekanbaru. The data used are primary data and secondary from central bodies and official statistics of industry and trade Pekanbaru city. The method used to analyze data is descriptive quantitative and financial feasibility analysis such as Net Present Value, Benefit Cost Ratio, Net Benefit Cost Ratio and Internal Rate Of Return. In this study, the population is all businessmen leather shoes in the city of Pekanbaru in 2014/2015 and carried out a census of the technique that is 13 businessmen. From the results of the study with method financial feasibility analysis Net Present Value, the value of business industry leather shoes of 8.449.371 is greater than zero means worthy to be developed. According to the results of the Benefit Cost Ratio obtained the value of 1,01 as well as the results of the calculation of Net Benefit Cost Ratio obtained the value of 1,34 more than zero, means business is worthy to be developed. Then from the results of the Internal Rate Of Return it is known to the rate of 29,68% bigger than interest rate is 16% then it is worthy to be developed. So a leather shoes business in the city of Pekanbaru have a good prospect and deserves to be developed, because it can provide jobs as well as impact to the revenue for that business it self.Keywords: prospect, leather shoes, material, capital, and financial analysis